Last Glacial Maximum to Holocene paleoceanography of the northwestern Ross Sea inferred from sediment core geochemistry and micropaleontology at Hallett Ridge - Melis R.; Capotondi L.; Torricella F.; Ferretti P.; Geniram A.; Kuk Hong J.; Kuhn G.; Khim B. -K.; Kim S.; Malinverno E.; Yoo K. C.; Colizza E. (Journal of Micropalaeontology, 2021)
During the Late Pleistocene Holocene, the Ross Sea Ice Shelf exhibited strong spatial variability in relation to the atmospheric and oceanographic climatic variations. Despite being thoroughly investigated, the timing of the ice sheet retreat from the outer continental shelf since the Last Glacial Maximum (LGM) still remains controversial, mainly due to a lack of sediment cores with a robust chronostratigraphy. For this reason, the recent recovery of sediments containing a continuous occurrence of calcareous foraminifera provides the important opportunity to create a reliable age model and document the early deglacial phase in particular. Here we present a multiproxy study from a sediment core collected at the Hallett Ridge (1800 m of depth), where significant occurrences of calcareous planktonic and benthic foraminifera allow us to document the first evidence of the deglaciation after the LGM at about 20.2 ka. Our results suggest that the co-occurrence of large Neogloboquadrina pachyderma tests and abundant juvenile forms reflects the beginning of open-water conditions and coverage of seasonal sea ice. Our multiproxy approach based on diatoms, silicoflagellates, carbon and oxygen stable isotopes on N. pachyderma, sediment texture, and geochemistry indicates that abrupt warming occurred at approximately 17.8 ka, followed by a period of increasing biological productivity. During the Holocene, the exclusive dominance of agglutinated benthic foraminifera suggests that dissolution was the main controlling factor on calcareous test accumulation and preservation. Diatoms and silicoflagellates show that ocean conditions were variable during the middle Holocene and the beginning of the Neoglacial period at around 4 ka. In the Neoglacial, an increase in sand content testifies to a strengthening of bottom-water currents, supported by an increase in the abundance of the tycopelagic fossil diatom Paralia sulcata transported from the coastal regions, while an increase in ice-rafted debris suggests more glacial transport by ...